The organization training process system for young hockey players through speed qualities development by the means of "Ice track" - Kosheleva, M. V.; Khorosheva, T. A.; Lazunina, I. V.; Romenskaya, O. V.; Nazarenko, N. N. (Journal of Human Sport & Exercise, 2020)
The article analyses the data obtained by the sigma sports pulsometer of pc15 with the author's technology realization within the speed endurance development for 10-11-year-old hockey players by means of a specialized hockey track. There is a description of the narrative and final results for each technology (program) stage. Within the stages of the pedagogical experiment, there was a classification test of physical development, which allowed us to speak about the effectiveness of the technology in use.